Significance of intellectual freedom in libraries: Perspectives of librarians in Kwara State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study investigates the perspectives of librarians in Kwara State on the significance of intellectual freedom. Four (4) objectives and questions were raised to achieve its purposes. A descriptive survey design was employed involving 183 members of the Nigerian Library Association (NLA), Kwara State chapter. A sample size calculator was used to select 53 respondents who were randomly sampled across librarians in Kwara State. Questionnaire were administered, and 39 questionnaires were returned, representing 71.73% response rate. Findings indicate that librarians in Kwara State understand intellectual freedom primarily as the right to access information and ideas without regard to the originator's perspective or the contents nature. The processes librarians in Kwara State used to promote intellectual freedom include developing library collections that reflect equity and inclusion, provision of equal access to the library’s information resources and teaching information skills. However, librarians in Kwara State perceived that the significance of intellectual freedom is difficult to achieve because of lack of demand for the information materials available in libraries, poor reviews about the information materials housed in libraries and low library budget to acquire all types of information materials. This study concluded that intellectual freedom is an important component of every society that is built on the tenets of justice, equity, equality and inclusion and because libraries are information provision institutions, librarians have crucial roles to play in making society members acknowledge and appreciate it.